Injection site sarcomas in other species than the domestic cat - STANS, J (Journal of the Hellenic Veterinary Medical Society, 2021)
Injection site sarcomas (ISS) are tumours of tissues of mesenchymal origin that occur at an injection site. These tumours have been mainly described in cats as Feline injection-site sarcoma (FISS), but suspected cases have also been described in other species such as dogs. In other species than the domestic cat, these tumours are however much rarer. As a result, the body of literature is limited. This review aims to summarize the knowledge regarding ISS in species other than the domestic cat. In general, it seems that ISS can occur in a wide range of animals and that similar treatment strategies are employed as in cats. Like in cats, it seems that the benefit of the reasons for injection (such as vaccination and microchip implantation) could outweigh the risk of ISS development in other species.